Eesti usukeel – quo vadis? - Rutiku, Siret (Usuteaduslik Ajakiri, 2003)
Siret Rutiku, The Estonian Language of Religion - quo uadis? The article introduces the aims of the Estonian Science Foundation grant No. 5292 The structure and development of theological and religious vocabulary in the Estonian language and work done thus far. The main aim of the four-year research project is to organise Estonian theological and religious vocabulary as well as open this field - which has not been studied widely in Estonia before - to interdisciplinary research. In the framework of the grant a computer-based terminology database has been compiled and systematised since June 2003. The article focuses on the principles and problems of compiling this database.